Employee Loyalty Determinants at KSPPS BTM Pekalongan: Job Satisfaction as a Mediating Variable (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
Many Sharia Microfinance Institutions in Indonesia have the form of KSPPS. Employee loyalty is very important in financial institutions of any kind. Employee loyalty in financial institutions is not only expected to be able to produce satisfactory performance but also to prevent fraud. This research aims to analyze the effect of HR competency and quality of work life on employee loyalty with job satisfaction as a mediating variable in KSPPS BTM Pekalongan employees. This research is field research with a quantitative approach. The population in this research amounted to 192 employees from the entire office network of KSPPS BTM Pekalongan. The sample in this research amounted to 130 employees determined based on the results of the calculation of the Slovin formula with a margin of error of 5%. Sampling in this research uses a proportional random sampling technique. The data collection technique in this research used a questionnaire with a Likert scale. The data analysis technique used in this research is path analysis. The results showed that HR competency and quality of work life have a significant effect on job satisfaction. HR competency, quality of work life, and job satisfaction have a significant effect on employee loyalty. Job satisfaction mediates the effect of HR competency and quality of work life on employee loyalty.